From Rarity to Recognition: Infantile Botulism and the Broad Spectrum of Differential Diagnoses - Matthew C. Authement; Brandon M. Jones; Robert J. Kahoud; Elizabeth H. Ristagno (Case Reports in Pediatrics)
This case illustrates a 5-week-old girl who presented with decreased activity, decreased feeds, poor suck, weak cry, lethargy, hypotonia, and areflexia. The child was found to have infant botulism. The case demonstrates the importance of a full history and broad differential in an ill-appearing infant. The differential for an ill-appearing infant should always include infectious etiologies and may include metabolic disorders, congenital anomalies, nonaccidental trauma, neurologic disorders, and endocrine disorders. The broad differential diagnosis may make rapid diagnosis and treatment for infantile botulism a challenge.